النعت في اللغة العربية و اللغة الإنجليزية - Fitriani (Departemen Sastra Asia Barat, Fakultas Ilmu budaya, Universitas Hasanuddin, 2023)
This study explains about comparative between na’t in Arabic and adjective in English. The study was conducted because of fundamental differences in the grammatical system of the two languages, including in classification of word, especially adjective. And the purpose of this study is to explain about adjective structure in Arabic, adjective structure in English, and to analyze adjective similarities and differences of the two languages. And the method of the study is library research. And the data collection method used is listening and analyzed with contrastive analysis or comparative analysis, so the data will be classified in two kinds, they are similarities data and differences data. As the result of this study, adjective structure in Arabic is classified into category (type and former), inflection (form, number, and type), position (after and before noun), and comparative word (Ism at-tafdhil). And adjective structure in English is classified into category (Limiting Adjective and Descriptive Adjective), inflection (form, number, and type), and comparative word (comparison). And the similarties of the two languages are based on: category (descriptive adjective), form (ma’rifah/nakirah and definite/indefinite), position (after and before noun), and comparative word by the level, whereas the differences are based on: category (limiting adjective), number, type, and comparative word on the additional word of adjective and irregular adjective. Keywords: Adjective, Language, Comparative